Slovenska umetnostna zgodovina in težave z metodologijo - Grafenauer, Petja (Monitor ISH, 2006)
The paper seeks to present a survey of the art historical methods used in Slovenia, focusing on those applied to modernism and contemporary art. Compared with the global state-of-the-art, the art historical methodology in Slovenia is rather underdeveloped, especially as practised in the central institutions of art historical research. Despite the influential pioneer work contributed by Izidor Cankar, the notion that art history is a historical science independent of theory prevailed well into the second half of the 20th century. It is only since the 1970s that contemporary art historical methods have begun to register in the practice of individual art historians.
Keywords: slovenska umetnost; art history; umetnostna zgodovina; metodologija; teorija; theory